Efficiency of Bacillus Licheniformis to Reduce Aflatoxin B1 Produced by Aspergillus Flavus - Risan, Mohsen H; Muhsin, Athraa H (Al-Nahrain Journal of Science, 2018)
This study aimed to evaluate efficiency of the bioproduct of the bacterium B. licheniformis to degrade aflatoxin B1 produced by A. flavus. Results showed that 11 isolates belonging to the genus Aspergillus spp. Five isolates diagnosed as A. flavus and 5 isolates as A. niger. Colonies were identified by morphological characteristics, colony characterized of A. flavus were Yellow - Green color on PDA medium. The bacterium B. licheniformis is highly effective in inhibiting the fungus A. flavus p3 in the culture medium. Percentage of inhibition zone reached 85% caused by the fungus A. flavus compared with the control. The medium Aspergillus flavus parasiticus agar (AFPA) was used to test the ability of A. flavus for aflatoxin production. A. flavus varied in producing aflatoxin. Results revealed that the three isolates P2, P3 and P7 are aflatoxin producers, but P6 and P11 can't produce aflatoxin. On the other hand, results showed variation in A. flavus isolates in producing the aflatoxin. The isolate (P3) was more produce able of aflatoxin. Moreover, Results showed aflatoxin B1 after the treatment with the fungus A. flavus, recorded 32µg/kg, compared to treatment with B. licheniformis + A. flavus and the control treatment.